2002
DOI: 10.1111/1469-8986.3920166
|View full text |Cite
|
Sign up to set email alerts
|

Reduced sensory anticipation in migraine

Abstract: We examined differences between migraine patients and matched healthy controls in anticipatory processes preceding a warning stimulus and preceding a response stimulus during a forewarned choice reaction time task. We manipulated stimulus preceding negativity~SPN! by inserting full response information either at the instant of the warning stimulus cue! or at the instant of the response stimulus. In contrast to control subjects, migraineurs with aura show low anticipation towards an informative cue and high ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…These are classically transient, and are thought to occur as the result of cortical phenomena 34‐36 . Motor symptoms of aura have been classified as an atypical aura as hemiplegic migraine 34‐36 . The latency change observed in this study suggests that there is motor dysfunction in children with migraine.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…These are classically transient, and are thought to occur as the result of cortical phenomena 34‐36 . Motor symptoms of aura have been classified as an atypical aura as hemiplegic migraine 34‐36 . The latency change observed in this study suggests that there is motor dysfunction in children with migraine.…”
Section: Discussionmentioning
confidence: 65%
“…2). Though the cerebral mechanisms of the latency changes remain unclear, it is widely recognized that neurologic symptoms are a prominent and often disturbing component of the migraine syndrome in many patients 34‐36 . Migraine‐related neurologic symptoms include visual, sensory, language, and motor disturbance, occurring in about one‐quarter of migraine patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research with agents affecting other neurotransmitters such as serotonin, noradrenaline and acetylcholine showed that the influence on the CNV is indirect (through interactions with the dopamine system), absent or dose dependent (Ashton et al 1976, 1980; Ashton and Rawlins 1978; Hansenne et al 2000; Mulder et al 2002). Benzodiazepines decrease CNV amplitude (Ashton et al 1976; Papart et al 1997; Rockstroh et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Anticipation to upcoming non‐painful experimental sensory events in migraineurs during the interictal state has been extensively investigated by neurophysiological tools providing strong evidence for the existence of enhanced sensory anticipation in these patients. Using non‐painful auditory stimuli, several studies pointed on 2 main abnormalities in anticipation event related potential (ERP) components in migraineurs as compared with the non‐migraine controls, increased amplitudes of contingent negative variation waves reflecting substantially enhanced motor readiness and anticipatory attention to imperative stimuli, and reduced amplitudes of stimulus preceding negativity (SPN) waves reflecting expectancy of upcoming response‐related reinforcement . Further neurophysiological evidence regarding the impact of anticipation in migraine came from experimental pain studies.…”
mentioning
confidence: 99%